Effect of zirconium oxide and zinc oxide nanoparticles on physicochemical properties and antibiofilm activity of a calcium silicate-based material - Tanomaru, Juliane Maria Guerreiro [UNESP]; Trindade-Junior, Adinael [UNESP]; Costa, Bernardo Cesar [UNESP]; Silva, Guilherme Ferreira da [UNESP]; Cifali, Leonardo Drullis [UNESP]; Bernardi, Maria Inês Basso; Tanomaru-Filho, Mario [UNESP] (Hindawi, 2014)
The aim of the present study was to evaluate the antibiofilm activity against Enterococcus faecalis, compressive strength. and radiopacity of Portland cement (PC) added to zirconium oxide (ZrO2), as radiopacifier, with or without nanoparticulated zinc oxide (ZnO).The following experimental materials were evaluated: PC, PC + ZrO2, PC + ZrO2 + ZnO (5%), and PC + ZrO2 + ZnO (10%). Antibiofilm activity was analyzed by using direct contact test (DCT) on Enterococcus faecalis biofilm, for 5 h or 15 h. The analysis was conducted by using the number of colony-forming units (CFU/mL). The compressive strength was performed in a mechanical testing machine. For the radiopacity tests, the specimens were radiographed together with an aluminium stepwedge. The results were submitted to ANOVA and Tukey tests, with level of significance at 5%. The results showed that all materials presented similar antibiofilm activity (𝑃 > 0.05). The addition of nanoparticulated ZnO decreased the compressive strength of PC. All materials presented higher radiopacity than pure PC. It can be concluded that the addition of ZrO2 and ZnO does not interfere with the antibiofilm activity and provides radiopacity to Portland cement. However, the presence of ZnO (5% or 10%) significantly decreased the compressive strength of the materials.
Keywords: Antimicrobial activity; Enterococcus faecalis; Radiopacity; Portland cement